Revisiting Critical Thinking in Early Childhood: A Bibliometric Review of Trends During and After COVID-19 Pandemic - William Ben Gunawan; Eka Anggraeny (Lia Center of Research and Education, 2026)
Critical thinking is increasingly recognized as a foundational competence that can be fostered from early childhood. The COVID-19 pandemic intensified scholarly attention to this area by disrupting early childhood education while accelerating pedagogical and technological innovation. This study revisits research trends and thematic developments on critical thinking in early childhood education during and after the COVID-19 period. Using a mixed-method design, the study integrates bibliometric analysis and a narrative literature review of 309 Scopus-indexed publications (2019-2026), analyzed using VOSviewer to identify publication growth, influential sources, subject areas, keyword co-occurrence, and temporal thematic shifts, while the narrative review synthesized recent empirical and conceptual studies. The findings show steady publication growth during COVID-19 and a marked surge in the post-pandemic period, with a substantial increase culminating in a publication peak in 2025. Research themes evolved from assessment, health-related issues, and emergency digital learning toward pedagogical refinement, teacher professional development, early childhood–specific interventions, and ethical integration of digital and AI-based tools. Overall, the literature reflects a shift toward understanding critical thinking as a socially mediated, context-dependent, and developmentally appropriate competence in early childhood education.